Diversidade escura e perturbação antrópica ligada a fatores abióticos e distúrbios crônicos e agudos nas florestas secas da Caatinga do Ceará - Araújo, Magno Daniel de Oliveira Gonçalves (2022)
Achieving conservation goals and prioritizing efforts requires appropriate metrics to quantify biodiversity. The most commonly used measure is the observed species richness, but it does not take into account the missing part of the species pool, i.e., dark diversity, nor the completeness of the community. For this reason, evaluating the drivers of these diversity indices is the basis for understanding the mechanisms in the formation of diversity patterns through abiotic conditions and anthropogenic disturbances. Also understanding patterns of how abiotic conditions may be related to acute and chronic disturbances is critical for the Caatinga, as part of its vegetation cover is currently lost due to human occupation and the remaining habitat is under intense pressure. This thesis aims to (1) show whether the different factors of habitat losschronic anthropogenic disturbance are influenced by climate-soil resources and (2) whether climate-soil-disturbance factors influence observed diversity and dark, completeness and the species pool. We used the IFN database (<Inventário Florestal Nacional=), which comprises 145 plots of 20 km x 20 km of the plant community of the Caatinga in the state of Ceará. Our study shows that (i) humans activities tend to disturb wetter areas and preferentially deforest wetter areas under fertile soils. Specifically, areas with more resources for human occupation possibly led to an increase in the density of people and animals within the Caatinga vegetation stands, supporting a causal relationship between the settlement of the human population and the degradation of the Caatinga vegetation. (ii) In general, rainfall and habitat amount best explain the observed and dark diversity in the Caatinga of Ceará, and plant life forms tend to respond differently to environmental variables. For example, while trees tend to be richer in wetter areas, herbs tend to be richer in drier areas. These results highlight the importance of calculating different species richness metrics and considering different groups of plant communities.